Would you admit your mother to the residency service? Introducing the JCHIMP resident safety column - Paul N. Foster (Greater Baltimore Medical Center, 2014)
There remain tremendous opportunities to improve the stability and safety of American health care. Within this context, residents and residency programs face two essential questions: how to reduce the risk to patients resulting from resident inexperience, and how to change our programs to create the safer physician of the future? The spread of side-by-side teaching and non-teaching services creates a natural setting to study these questions and improve both services. When asked the question, "Would you admit your mother to the resident service?", many of us respond, "It depends". We are focusing this column on helping programs answer this question definitively in the positive, share potential best practices, and underscore community hospital's contribution to our understanding of patient safety.